The effects of various enzymatic saccharifications and microwave pretreatment durations on sugar yield and its property alterations of Chinese spirits distillers residues. Issue 1 (31st December 2022) - Zeng, Huawei; He, Hongkui; Ma, Jingtong; Cao, Runjie; Zeng, Xin; Xin, Bingyue; Wang, Yanwen; Qiao, Jie; Zhou, Shen; Dong, Tingting; Li, Anjun; Yin, Xian
Abstract : This study evaluated the effect of different enzymatic hydrolysis and different microwave pretreatment durations on the sugar yield of Chinese spirits distillers residues (CSDR). Addition of both α-amylase and cellulase in the enzymatic hydrolysis of distillers grains resulted in a higher yield of reducing sugar (145.74 ± 4.20 mg·g –1 ). Fourier transform infrared spectroscopy (FTIR) revealed that different enzyme treatments degraded different functional groups of the cellulose structure. Subsequently, the highest reducing sugar yield (181.33 ± 6.42 mg·g –1 ) was achieved at microwave pretreatment time of 6 min and was 1.29-fold higher than that of the untreated sample. The differences in the structural features of CSDRs under various microwave pretreatment durations were characterized by scanning electron microscopy, FTIR spectroscopy, and X-ray diffraction. The data revealed that the optimal microwave pretreatment time at 6 min could obviously remove lignin, and then obtain the highest CrI value, achieving the highest reducing sugar yield.